The relationship between image and reputation in the Spanish public university - Cristina Del-Castillo-Feito; Alicia Blanco-González; Encarnación González-Vázquez (European Research on Management and Business Economics (ERMBE), 2019)
The correct management of reputation and image can be crucial to guarantee organizationś survival and success. However, the lack of clarity regarding the relationship and differences between image and reputation still exist since scholars have considered them related constructs with differences and used them interchangeably. Spanish Public Universities operate in a highly competitive sector where factors such as globalization as well as the decrease in government funding have strengthen this situation. Therefore, the aim of this paper is to measure the relationship between image and reputation in the context of Spanish Public Universities considering different university's stakeholder perceptions (students, alumni, professors, support personnel and managers). To pursue this objective, a review of literature on image and reputation was developed, followed by the distribution of 870 surveys to a Spanish Public University's stakeholders. Finally, PLS-SEM was used to analyse the data and confirm the existing relationship between image and reputation.
Keywords: M10; M31; L38; I23; 650; Higher education; Image; Reputation; Spain; University